The External Environment as Driving To Organizational Change Under Internal Environment's Adaptation: "Empirical Evidence From Commercial Banks’ adoption of Islamic Financial Transactions In Libya” - Salwa Abdel Gader Khalleefah, Bin Idrees; Syed Musa, Alhabshi; Sharofiddin, Ashurov; Abdullah Othman, Anwar Hasan (2021)
The Issue Under Study and Search Gap Literary review to define the Conceptual Framework of the study Hypothesized Modelling Adopted Methodology Results and Discussions of Hypothesized Modelling Conclusion and Horizons for future research